2022
DOI: 10.1186/s13024-022-00558-4
|View full text |Cite
|
Sign up to set email alerts
|

Elevated ganglioside GM2 activator (GM2A) in human brain tissue reduces neurite integrity and spontaneous neuronal activity

Abstract: Background Alzheimer’s Disease (AD) affects millions globally, but therapy development is lagging. New experimental systems that monitor neuronal functions in conditions approximating the AD brain may be beneficial for identifying new therapeutic strategies. Methods We expose cultured neurons to aqueous-soluble human brain extract from 43 individuals across a spectrum of AD pathology. Multi-electrode arrays (MEAs) and live-cell imaging were used to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 53 publications
0
6
0
Order By: Relevance
“…[ 37 ] GM2A is a lipid transfer protein that stimulates the enzymatic processing of gangliosides and activates T cells via lipid presentation while acting as a gene encoding lysosomal enzyme. [ 38 ] Katarzyna et al [ 39 , 40 ] demonstrated that GM2A was up-regulated in an in vitro psoriatic model established using Hacat cells. MMP12 (human macrophage metalloproteinase) has been identified as an elastolytic metalloproteinase secreted by inflammatory macrophages [ 41 ] ; the levels of MMP12 messenger RNA (mRNA) were 17-fold higher in psoriatic lesions than in NL skin.…”
Section: Resultsmentioning
confidence: 99%
“…[ 37 ] GM2A is a lipid transfer protein that stimulates the enzymatic processing of gangliosides and activates T cells via lipid presentation while acting as a gene encoding lysosomal enzyme. [ 38 ] Katarzyna et al [ 39 , 40 ] demonstrated that GM2A was up-regulated in an in vitro psoriatic model established using Hacat cells. MMP12 (human macrophage metalloproteinase) has been identified as an elastolytic metalloproteinase secreted by inflammatory macrophages [ 41 ] ; the levels of MMP12 messenger RNA (mRNA) were 17-fold higher in psoriatic lesions than in NL skin.…”
Section: Resultsmentioning
confidence: 99%
“…Elevated levels of GM2A in culture reduce neurite extension and neuronal firing rate, which may be beneficial in the context of pain and dorsal horn circuitry. 71 …”
Section: Discussionmentioning
confidence: 99%
“…To exclude artifacts arising due to postmortem delays and/or freeze-thawing of tissue, for certain studies it will be important to investigate the use of fresh biopsy tissue. Nonetheless, other investigators have already employed our experimental paradigms ( Sideris et al, 2021 ; Emin et al, 2022 ; Hsieh et al, 2022 ; Liu et al, 2022 ; Stern et al, 2022 ) and we expect that these protocols will be further exploited. For instance to examine the bioactivity of tau and α-synuclein ( Corbett et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%